DNA micelle flares: a study of the basic properties that contribute to enhanced stability and binding affinity in complex biological systems. Issue 9 (10th June 2016) - Wang, Yanyue; Wu, Cuichen; Chen, Tao; Sun, Hao; Cansiz, Sena; Zhang, Liqin; Cui, Cheng; Hou, Weijia; Wu, Yuan; Wan, Shuo; Cai, Ren; Liu, Yuan; et al.
Abstract : DMFs are spherical DNA–diacyllipid nanostructures formed by hydrophobic effects between lipid tails coupled to single-stranded DNAs. Abstract : DMFs are spherical DNA–diacyllipid nanostructures formed by hydrophobic effects between lipid tails coupled to single-stranded DNAs. Such properties as high cellular permeability, low critical micelle concentration (CMC) and facile fabrication facilitate intracellular imaging and drug delivery. While the basic properties of NFs have been amply described and tested, few studies have characterized the fundamental properties of DMFs with particular respect to aggregation number, dissociation constant and biostability. Therefore, to further explore their conformational features and enhanced stability in complex biological systems, we herein report a series of characterization studies. Static light scattering (SLS) demonstrated that DMFs possess greater DNA loading capacity when compared to other DNA-based nanostructures. Upon binding to complementary DNA (cDNA), DMFs showed excellent dissociation constants ( K d ) and increased melting temperatures, as well as constant CMC (10 nM) independent of DNA length. DMFs also present significantly enhanced stability in aqueous solution with nuclease and cell lysate. These properties make DMFs ideal for versatile applications in bioanalysis and theranostics studies.